Patriotic motives in satirical works of Volodymyr Vynnychenko (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The author of the article accents that V.  Vynnychenko’s trouble according the pureness, moral irreproachability of those who declared themselves as the upholders of embodiment of high ideals stipulates rather wide appeal of the writer to the satire in his works of the patriotic topics. Critic analyzes in details from such aspect the short stories “Maloros-European” and “Theatrical enterpriser Harkun-Zadunaysky”.
Keywords: Vynnychenko; early prose; patriotic motives; satire